2005
DOI: 10.1089/aid.2005.21.263
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the Dose of Hydroxyurea Minimizes Toxicity and Maximizes Anti-HIV Potency

Abstract: The goal of this study was to optimize the hydroxyurea dosage in HIV-infected patients, and to minimize the toxicity and maximize the antiviral efficacy of the hydroxyurea-didanosine combination. In a randomized, open-label study (RIGHT 702, a multicenter trial performed in private and institutional practices), three daily doses (600 microg, 800-900 microg, and 1200 microg) of hydroxyurea were administered in combination with didanosine and stavudine to 115 chronically HIV-infected patients, one-third antiretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…In order to prove the hypothesis and to clarify which component was responsible for the elevated pancreatic toxicity, Foli et al assessed the in vitro effects of hydroxyurea and didanosine concentrations For these reasons RIGHT 702, a phase I/II randomized, open-label, dose regimen study with 115 HIV-1 infected patients was designed to determine the best total daily dose and the best dosing interval of hydroxyurea, in combination with didanosine and stavudine. This study demonstrated that hydroxyurea when administered at a low dose (600mg total daily) is safer and more efficacious than higher doses (800-900mg and 1,200mg) for the treatment of HIV [44]. 400mg QD didanosine administered as an enteric coated capsule in combination with the lowest hydroxyurea dose (600mg hydroxyurea) was the best tolerated, had fewer side effects and was the most potent by all efficacy parameters analyzed, including the proportion of patients with viremia <400 copies/ml at week 24 (primary endpoint), mean area under the curve (AUC), mean log 10 decrease, increase in CD4 and decrease in CD8 count.…”
Section: Dose Finding Studies Of Hydroxyurea-didanosine Combinationmentioning
confidence: 73%
“…In order to prove the hypothesis and to clarify which component was responsible for the elevated pancreatic toxicity, Foli et al assessed the in vitro effects of hydroxyurea and didanosine concentrations For these reasons RIGHT 702, a phase I/II randomized, open-label, dose regimen study with 115 HIV-1 infected patients was designed to determine the best total daily dose and the best dosing interval of hydroxyurea, in combination with didanosine and stavudine. This study demonstrated that hydroxyurea when administered at a low dose (600mg total daily) is safer and more efficacious than higher doses (800-900mg and 1,200mg) for the treatment of HIV [44]. 400mg QD didanosine administered as an enteric coated capsule in combination with the lowest hydroxyurea dose (600mg hydroxyurea) was the best tolerated, had fewer side effects and was the most potent by all efficacy parameters analyzed, including the proportion of patients with viremia <400 copies/ml at week 24 (primary endpoint), mean area under the curve (AUC), mean log 10 decrease, increase in CD4 and decrease in CD8 count.…”
Section: Dose Finding Studies Of Hydroxyurea-didanosine Combinationmentioning
confidence: 73%
“…Through the flexibility of the VS411 formulation, it is possible to reduce the dose of HU in order to potentially limit toxicities. A reduction in HU dosage is supported by the results of the RIGHT 702 study which demonstrated that a lower HU dose of 600 mg daily achieved better antiretroviral activity than did higher doses of 800–1200 mg, together with a better CD4+ cell count increase and fewer adverse effects (Lori et al ., 2005b). This was consistent with the in vitro observation that decreasing HU concentrations are associated with the transition from cytotoxic (50–100 µM) to cytostatic (10 µM) effects (Lori et al ., 2005a), indicating that lowering HU doses may be an option in combination with ddI.…”
Section: Discussionmentioning
confidence: 97%
“…For HU, the relationship between dosage and toxicity has already been established (Lori et al ., 2005b), although a clear relation between the maximal plasma concentration ( C max ) and adverse events has not been proven. HU is generally well tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…There was a study that showed that a dose of 600mg daily was better tolerated and most effective in improving HIV status. 22 Dosing for psoriasis in the general population usually was 1.0–1.5g/day. However, if hydroxyurea therapy is initiated, our recommendation is a low dose of hydroxyurea 500mg daily, which can be slowly titrated up to minimize hematologic adverse events in a HIV-infected individual.…”
Section: Discussionmentioning
confidence: 99%